Bio-efficacy and economics of newer insecticides against whitefly (Trialeurodes ricini) infesting castor: BIO-EFFICACY AND ECONOMICS OF NEWER INSECTICIDES AGAINST WHITEFLY INFESTING CASTOR - M SENTHIL KUMAR (Journal of Oilseeds Research, 2018)
A field experiment was conducted to evaluate the efficacy of newer insecticides against whitefly in castor during kharif season 2016 and 2017 at Tapioca andCastor Research Station,Tamil Nadu Agricultural University, Yethapur, Tamil Nadu. Based on whiteflies number/3 leaves/plant and per cent reduction over control recorded after two sprays concluded that all the treatments showed significant difference in reducing whiteflies over control. Among the insecticides, buprofezin 25 SC @ 0.8ml/l was found significantly most effective followed by profenophos 50 EC @ 2ml/l, imidacloprid 17.8 SL@0.5ml/l, dimethoate 30 EC @ 1.7ml/l and flonicamid 50 WG@0.2g/l for reducing the whiteflies population. Highest seed yield was obtained with buprofezin 25 SC @ 0.8 ml/l (2034 kg/ha) followed by flonicamid 50 WG @ 0.2g/l (1723 kg/ha) as against 694 kg/ha in untreated control. The maximum incremental cost-benefit ratio of 1: 16.74 was obtained with application of buprofezin 25 SC @ 0.8 ml/l.